2023
DOI: 10.3390/ijms241310946
|View full text |Cite
|
Sign up to set email alerts
|

Phototherapy of Alzheimer’s Disease: Photostimulation of Brain Lymphatics during Sleep: A Systematic Review

Abstract: The global number of people with Alzheimer’s disease (AD) doubles every 5 years. It has been established that unless an effective treatment for AD is found, the incidence of AD will triple by 2060. However, pharmacological therapies for AD have failed to show effectiveness and safety. Therefore, the search for alternative methods for treating AD is an urgent problem in medicine. The lymphatic drainage and removal system of the brain (LDRSB) plays an important role in resistance to the progression of AD. The de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 175 publications
0
23
0
Order By: Relevance
“…Typically, in experimental and clinical studies, PBM is performed in awake subjects [ 15 , 30 38 ]. In our recent review, we suggested that there are no commercial devices for simultaneous PBM and sleep monitoring, which significantly limits the clinical investigations the therapeutic effects of PBM during sleep [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Typically, in experimental and clinical studies, PBM is performed in awake subjects [ 15 , 30 38 ]. In our recent review, we suggested that there are no commercial devices for simultaneous PBM and sleep monitoring, which significantly limits the clinical investigations the therapeutic effects of PBM during sleep [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our recent review, we suggested that there are no commercial devices for simultaneous PBM and sleep monitoring, which significantly limits the clinical investigations the therapeutic effects of PBM during sleep [ 16 ]. We discussed that the development of sleep-PBM technologies is urgently needed and could become a breakthrough step in the progress of AD therapy in humans [ 15 , 16 ]. The technology proposed in this study opens new perspectives of development of promising PBM devices for night phototherapy of brain diseases and its implementation in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations